Museum: Sumber Belajar dan Pariwisata Sejarah Budaya di Kota Lubuklinggau - Ratna Wulan Sari; Andriana Sofiarini (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
Museums are locations that store various collections of cultural and historical heritage, have great potential to attract tourists. Lubuklinggau city students and students utilize the museum as a place of learning to know and understand the heritage that is in the museum. The museum in Lubuklinggau city is the Subkos museum which is located in the center of Lubuiklinggau city. Visiting a museum is not just coming, but also a process of understanding, learning, and appreciating the history and culture that we encounter in various museum collections. Unfortunately, the existence of museums is still not considered by the community, especially in its utilization as a learning tool. The management of existing museums needs to be well organized and adapted to the times. Nowadays, museums do not only focus on collections, but on how to attract visitors and make them an educational resource. This research adopts a qualitative method. The data used consists of two types: first, primary data obtained through direct interviews with museum managers, and second, secondary data taken from articles in relevant journals.